2018
DOI: 10.1007/s00592-018-1204-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vildagliptin versus glibenclamide on endothelial function and arterial stiffness in patients with type 2 diabetes and hypertension: a randomized controlled trial

Abstract: ClinicalTrials.gov: NCT02145611, registered on 11 Jun 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Some of us have previously shown that metformin did not affect significantly PWV over a period of 6 months in drug‐naïve patients with T2DM, while in a recently published sub‐analysis of the Maastricht Study, it was demonstrated that metformin use did not feature a significant impact on aortic stiffness . As far as sulphonylureas are concerned, it has been previously shown that glibenclamide does not affect augmentation index, compared to sitagliptin; however, in a more recent RCT it was demonstrated that glibenclamide significantly decreased ambulatory PWV after 12 weeks of treatment, although the effect was not significant when compared to vildagliptin . Regarding pioglitazone, existing evidence might be considered as old and limited; however, its significant effect on aortic stiffness has also been shown in a non‐diabetic population, namely in patients with rheumatoid arthritis …”
Section: The Effect Of Other Antidiabetics On Arterial Stiffnessmentioning
confidence: 96%
“…Some of us have previously shown that metformin did not affect significantly PWV over a period of 6 months in drug‐naïve patients with T2DM, while in a recently published sub‐analysis of the Maastricht Study, it was demonstrated that metformin use did not feature a significant impact on aortic stiffness . As far as sulphonylureas are concerned, it has been previously shown that glibenclamide does not affect augmentation index, compared to sitagliptin; however, in a more recent RCT it was demonstrated that glibenclamide significantly decreased ambulatory PWV after 12 weeks of treatment, although the effect was not significant when compared to vildagliptin . Regarding pioglitazone, existing evidence might be considered as old and limited; however, its significant effect on aortic stiffness has also been shown in a non‐diabetic population, namely in patients with rheumatoid arthritis …”
Section: The Effect Of Other Antidiabetics On Arterial Stiffnessmentioning
confidence: 96%
“…A total of 148 participants were invited to participate in this trial, 50 met the criteria for inclusion and were randomly assigned to the present study, as described in a previous study. 13 According to previous publication, no differences were described between the groups with respect to age, duration of T2DM or hypertension, office BP level, body mass index (BMI), HbA1c level, eGFR, lipid parameters, and microalbuminuria ( Table 1 ).…”
Section: Resultsmentioning
confidence: 94%
“…doi:10.1007/s00592-018-1204-1, COPYRIGHT (2018). 13 Abbreviations: BMI, body mass index; SBP, systolic blood pressure; DBP, diastolic blood pressure; FG, fasting glucose; TC, total cholesterol; LDLc, low-density lipoprotein cholesterol; HDLc, high-density lipoprotein cholesterol; TG, triglycerides; eGFR, estimated glomerular filtration rate; UA/Cr, urinary albumin-to-creatinine ratio. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might lead to in ated effect sizes. In addition, an interesting phenomenon was found: lowering BP and blood glucose using anti-hypertensive and anti-diabetic medications for weeks does not improve the RHI-measured ED [25][26][27][28] , but the short-term lowering of TG using feno brate could 29 , to some extent, do this. This signi es that high TG might be a more sensitive index, imposing a greater effect on the endothelium for a certain amount of time.…”
Section: Discussionmentioning
confidence: 99%